A Critical Analysis Of The Rights Of Divorced Woman Under Islamic Law - Hamidu Ardo; Abubakar Ibrahim Adamu (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
The phenomenon of marriage dissolution has existed before Islam and has persisted ever since. Indeed, if the contemporary world situation is indictable of any trend, it appears to foretell a continuing increase in divorce rates; the gradual decline in some societies is offset by the continuing rise in others. This paper investigates on critical analysis of the rights of divorced woman under Islamic Law. The paper start with brief introduction on the right of maintenance (shelter, clothing and food) in Revocable Divorce. The paper further explain the right to inheritance from divorced wife. The paper end with the analysis on the position of Divorcee in Islamic Law according to the views of Muslim Scholars and the right to demand payment for nursing and custodian of children of fail marriage. Analytical research methodology was used in this paper. Data are drawn from books, articles, scholarly journals etc.